4(w-2)=8w+4-2(-4w-3)

Simple and best practice solution for 4(w-2)=8w+4-2(-4w-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(w-2)=8w+4-2(-4w-3) equation:


Simplifying
4(w + -2) = 8w + 4 + -2(-4w + -3)

Reorder the terms:
4(-2 + w) = 8w + 4 + -2(-4w + -3)
(-2 * 4 + w * 4) = 8w + 4 + -2(-4w + -3)
(-8 + 4w) = 8w + 4 + -2(-4w + -3)

Reorder the terms:
-8 + 4w = 8w + 4 + -2(-3 + -4w)
-8 + 4w = 8w + 4 + (-3 * -2 + -4w * -2)
-8 + 4w = 8w + 4 + (6 + 8w)

Reorder the terms:
-8 + 4w = 4 + 6 + 8w + 8w

Combine like terms: 4 + 6 = 10
-8 + 4w = 10 + 8w + 8w

Combine like terms: 8w + 8w = 16w
-8 + 4w = 10 + 16w

Solving
-8 + 4w = 10 + 16w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-16w' to each side of the equation.
-8 + 4w + -16w = 10 + 16w + -16w

Combine like terms: 4w + -16w = -12w
-8 + -12w = 10 + 16w + -16w

Combine like terms: 16w + -16w = 0
-8 + -12w = 10 + 0
-8 + -12w = 10

Add '8' to each side of the equation.
-8 + 8 + -12w = 10 + 8

Combine like terms: -8 + 8 = 0
0 + -12w = 10 + 8
-12w = 10 + 8

Combine like terms: 10 + 8 = 18
-12w = 18

Divide each side by '-12'.
w = -1.5

Simplifying
w = -1.5

See similar equations:

| -4x+0=-7 | | 64a^2b-16a^3+18a^2b-9=0 | | 4x-2(x-9)=26 | | X-24=42 | | -4(6)+y=-7 | | 8(12+a)= | | -4x+4(-x-14)=-144 | | 2t^2/16t | | -3(5w-4)+9w=2(w+8) | | 5(3y-2)=(4y+4)+2y | | -4(5)+y=-7 | | -3(-7u+5)-5u=6(u-2)-5 | | 21=.5h(6+1) | | 6*-y=3 | | 4a+3a=-20 | | -2(y+1)=9y-2+2(2y+6) | | Y-x=-15 | | -39-26+x= | | 6x-6(-x+18)=12 | | 5(-2x+1)=35 | | .5(8-c)=7.5 | | 6y+6z=-1 | | .7(x-2)=3 | | 65=98 | | 4x+20y=3 | | X=1/180 | | y=f(x)+3 | | 5-3x=25 | | -2y-3(4-2Y)=2(y-3)+6 | | 2y+x(2-y)=9 | | 221=(4+x)(x) | | 7+2(2y-2)=-3(3y-6)+4y |

Equations solver categories